Classifications Of Voltage Stability Margin (VSM) And Load Power Margin (LPM) Using Probabilistic Neural Network (PNN) - Mohamad Nor, Ahmad Fateh; Sulaiman , Marizan; Abdul Kadir, Aida Fazliana; Omar, Rosli (Asian Research Publishing Network (ARPN), 2017)
-